Effects of Blood Flow Restriction on O2 Muscle Extraction and O2 Pulmonary Uptake Kinetics During Heavy Exercise - Salzmann, Killian; Sanchez, Anthony M. J.; Borrani, Fabio (Frontiers in Physiology, 2021)
This study aimed to determine the effects of three levels of blood flow restriction (BFR) on VO2 and O2 extraction kinetics during heavy cycling exercise transitions. Twelve healthy trained males completed two bouts of 10min heavy intensity exercise without BFR (CON), with 40% or 50% BFR (BFR40 and BFR50, respectively). VO2 and tissue saturation index (TSI) were continuously measured and modelled using multiexponential functions. The time constant of the VO2 primary phase was significantly slowed in BFR40 (26.4±2.0s; p<0.001) and BFR50 (27.1±2.1s; p=0.001) compared to CON (19.0±1.1s). The amplitude of the VO2 slow component was significantly increased (p<0.001) with BFR in a pressure-dependent manner (3.6±0.7, 6.7±0.9 and 9.7±1.0 ml.min-1.kg-1 for CON, BFR40, and BFR50, respectively. While no acceleration of the primary component of the TSI kinetics was observed, there was an increase (p<0.001) of the phase 3 amplitude with BFR (CON -0.8±0.3% VS BFR40 -2.9±0.9%, CON VS BFR50 -2.8±0.8%). It may be speculated that BFR applied during cycling exercise in the heavy intensity domain shifted the working muscles to an O2 dependent situation. The acceleration of the extraction kinetics could have reached a plateau, hence not permitting compensation for the slowdown of the blood flow kinetics, and slowing VO2 kinetics.